1986
DOI: 10.1002/bms.1200130209
|View full text |Cite
|
Sign up to set email alerts
|

Determination of polycyclic aromatic hydrocarbons in coal fly ash using gas chromatography/negative ion chemical ionization mass spectrometry

Abstract: This study reports studies using electron capture negative ion chemical ionization gas chromatographylmass spectrometry (EC-NICI G U M S ) of 21 polycyclic aromatic hydrocaroon (PAH) compounds. The selectivity and sensitivity of these compounds are shown here to be highly dependent on ion source temperature and pressure. Changes in selectivity arise from variations in instrumental parameters and can be largely explained by the competitive formation processes of [MI-' and[M-HIions. The formation of the adduct i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Non-reactive buffer gases, like methane, have been used to enhance negative ion formation by electron-capture reactions,3-' ' while reactive reagent gases, like oxygen or nitrous oxide, have been used to promote ionization by ion-molecule reactions.6"'-'8 Using methane as the buffer gas, it has been shown that PAH with calculated electron affinity (EA) values greater than about 0.5 eV produce abundant molecular ions, M -', 3 while PAH with EA values lower than 0.5 eV respond poorly. In some studies, PAH with low EA values have been observed to yield [M -HI-ions that have been attributed to deprotonation by basic species in the buffer gas5, 8 reported when the NICI spectra of PAH have been obtained using non-reactive gases. These ions have been attributed to reactions with either ionic species, generated from buffer gas impurities, or radical species, produced upon ionization of the buffer gas.…”
Section: Introductionmentioning
confidence: 98%
“…Non-reactive buffer gases, like methane, have been used to enhance negative ion formation by electron-capture reactions,3-' ' while reactive reagent gases, like oxygen or nitrous oxide, have been used to promote ionization by ion-molecule reactions.6"'-'8 Using methane as the buffer gas, it has been shown that PAH with calculated electron affinity (EA) values greater than about 0.5 eV produce abundant molecular ions, M -', 3 while PAH with EA values lower than 0.5 eV respond poorly. In some studies, PAH with low EA values have been observed to yield [M -HI-ions that have been attributed to deprotonation by basic species in the buffer gas5, 8 reported when the NICI spectra of PAH have been obtained using non-reactive gases. These ions have been attributed to reactions with either ionic species, generated from buffer gas impurities, or radical species, produced upon ionization of the buffer gas.…”
Section: Introductionmentioning
confidence: 98%
“…A variety of analytical methods has been used for determining trace concentrations of PAHs in environmental samples (Table 6- Oehme (1983) and Low et al (1986) employed capillary GC coupled with negative ion chemical ionization MS for detecting and differentiating isomeric PAHs (including PAHs on EPA's priority pollutant list). This procedure was successfully used to differentiate the isomers benzolj]fluoranthene and benzo [b]fluoranthene at low ppb levels in complex matrices, such as air particulate matter and coal fly ash.…”
Section: Environmental Samplesmentioning
confidence: 99%
“…The LOD for I[cd]P is lower by negative-ion chemical ionization than by positive-ion chemical ionization, but in the same time B[a]A is not detected by negative-ion chemical ionization mass spectrometry. As one can see from Table 2 the Table 6 Electron affinity (EA) of PAH (Low et al, 1986) and methane negative-ion chemical ionization mass spectra of PAH from the present work For the purpose of comparison, the content of PAHs found in various smoked fish products was confronted with data from literature. The levels of PAH in Estonian smoked fish in the present study are lower than those found in smoked fish from Japan (Masuda and Kuratsune, 1971), but show good agreement with results from Canada (Panalaks, 1976), Sweden (Larsson, 1982), Russia (Kim et al, 1999) and Italy (Moret et al, 1999).…”
Section: Article In Pressmentioning
confidence: 99%
“…Table 6 summarizes the fragment ions in the methane negative ion chemical ionization mass spectra of the six PAHs compounds studied. Table 5 Proton affinity (PA) of the PAH (Riahi and Sellier, 1998) (Low et al, 1986). The LOD and the LOQ has been established using spiked samples and determined by negative-ion chemical ionization.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation